Enhanced pulse shaping filters for minimizing interference in GFDM signals for 5G cellular networks - Tadikamalla, Sairam Vamsi; Mohanta, Harish Chandra; Terlapu, Sudheer Kumar; Mandhapati, Vamshi Krishna (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
The imminent rise of 5th generation (5G) wireless standards heralds a pivotal era in cellular communication. Among the challenges faced, selecting an optimal multiple access technique stands out as crucial for achieving the desired blend of low latency, high data rates, and throughput. Generalized frequency division multiplexing (GFDM) emerges as a promising can-didate meeting 5G requirements. This study introduces two innovative pulse shaping filters (PSFs) the better than raised cosine filter (BRCF) and modified bartlett hanning filter (MBHF) paired with various modulation schemes such as binary phase shift keying (BPSK), quadrature phase shift keying (QPSK), and quadrature amplitude modulation (QAM) to assess GFDM signal performance. Considering its spectrum efficiency, QAM modulation emerges as the preferred choice. Performance evaluation of the PSFs entails analyzing symbol error rate (SER) against signal to noise ratio (SNR) across different modulation schemes.